2011
DOI: 10.1038/jp.2011.187
|View full text |Cite
|
Sign up to set email alerts
|

Admission uric acid levels and length of expectant management in preterm preeclampsia

Abstract: Objective: Uric acid is known to be elevated in preeclampsia. We sought to determine if uric acid levels on admission correlate with the length of expectant management in preterm patients with preeclampsia.Study Design: A retrospective chart review was conducted on singleton preeclamptic pregnancies delivered between 24 0/7 and 37 0/7 weeks' gestation at Tufts Medical Center between January 2005 and December 2007. Patients with a multiple gestation and those transferred or discharged before delivery were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…However, SUA may be useful in predicting the length of the latency period from diagnosis to delivery. The author of another article [23] showed that admission uric acid levels correlate with the length of expectant management in preterm patients with preeclampsia. Pregnancy prolongation for > 1 week is significantly more likely in patients with low and medium uric acid levels at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…However, SUA may be useful in predicting the length of the latency period from diagnosis to delivery. The author of another article [23] showed that admission uric acid levels correlate with the length of expectant management in preterm patients with preeclampsia. Pregnancy prolongation for > 1 week is significantly more likely in patients with low and medium uric acid levels at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our capacity to predict severe maternal and perinatal outcomes remains poor [11], [12], [13]Several means of pre-clinical diagnosis and prognostic evaluation have been studied, such as Doppler ultrasound examination of umbilical or uterine arteries and biochemical markers (urinary protein, uric acid), with various degrees of predictive accuracy [14], [15], [16], [17]. This suggests that a pre-clinical diagnostic test able to predict maternal and fetal risk could be useful [18], [19]. Finally, patients who are evaluated for suspicion of preeclampsia undergo many exams, usually during in-hospital care, to assess or rule out the diagnosis of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation of a higher risk of pulmonary edema with increasing uric acid concentration may be that an elevated level of uric acid reflects preeclampsia severity, 14 and is negatively correlated with the duration of expectant management in women with preterm preeclampsia. 15 Only some of our cases, and none of our control subjects, underwent echocardiography; therefore, we could not properly contrast cardiac performance between the two groups. We also did not have pre-pregnancy or post-pregnancy measures of left ventricular function.…”
Section: Discussionmentioning
confidence: 95%